In vitro culture of Parthenium argentatum Gray : callus, suspension, protoplast culture and organogenesis - Trautmann, I. A.(Ilse Antoinette) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1990.